Ecosystem productivity and carbon cycling in intact and annually burnt forest at the dry southern limit of the Amazon rainforest (Mato Grosso, Brazil) - Rocha, Wanderley; Metcalfe, Daniel B.; Doughty, Chris E.; Brando, Paulo; Silvério, Divino; Halladay, Kate; Nepstad, Daniel C.; Balch, Jennifer K.; Malhi, Yadvinder (Plant ecology & diversity, 2014)
Background: The impact of fire on carbon cycling in tropical forests is potentially large, but remains poorly quantified, particularly in the locality of the transition forests that mark the boundaries between humid forests and savannas. Aims: To present the first comprehensive description of the impact of repeated low intensity, understorey fire on carbon cycling in a semi-deciduous, seasonally dry tropical forest on infertile soil in south-eastern Amazonia. Methods: We compared an annually burnt forest plot with a control plot over a three-year period (2009-2011). For each plot we quantified the components of net primary productivity (NPP), autotrophic (R a ) and heterotrophic respiration (R h ), and estimated total plant carbon expenditure (PCE, the sum of NPP and R a ) and carbon-use efficiency (CUE, the quotient of NPP/PCE). Results: Total NPP and R a were 15 and 4% lower on the burnt plot than on the control, respectively. Both plots were characterised by a slightly higher CUE of 0.36-0.39, compared to evergreen lowland Amazon forests. Conclusions: These measurements provide the first evidence of a distinctive pattern of carbon cycling within this transitional forest. Overall, regular understorey fire is shown to have little impact on ecosystem-level carbon fluxes.